2016
DOI: 10.2514/1.j054583
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Gradient and Nonadiabatic Surface Effects on Boundary Layer Transition

Abstract: The influence of the streamwise pressure gradient and a nonadiabatic surface on boundary layer transition was experimentally investigated at the Cryogenic Ludwieg-Tube Göttingen, Germany. Boundary layer transition was detected nonintrusively by means of the temperature-sensitive paint technique. The wind-tunnel model was designed to achieve a quasi-uniform streamwise pressure gradient over a large portion of the model chord length. This allowed the effects on boundary layer transition of the streamwise pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
58
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(59 citation statements)
references
References 28 publications
1
58
0
Order By: Relevance
“…Downstream of the leading edge region with x∕c > 20% , the pressure gradient is essentially uniform on a large portion of the upper surface. Only around x∕c = 35% the pressure distribution shows some slight variations from an ideally smooth one, due to a model part junction (Costantini et al 2015b(Costantini et al , 2016aCostantini 2016).…”
Section: The Two-dimensional Wind Tunnel Model Palastramentioning
confidence: 97%
See 2 more Smart Citations
“…Downstream of the leading edge region with x∕c > 20% , the pressure gradient is essentially uniform on a large portion of the upper surface. Only around x∕c = 35% the pressure distribution shows some slight variations from an ideally smooth one, due to a model part junction (Costantini et al 2015b(Costantini et al , 2016aCostantini 2016).…”
Section: The Two-dimensional Wind Tunnel Model Palastramentioning
confidence: 97%
“…The wind tunnel model used for the present study was the two-dimensional PaLASTra model (Costantini et al 2015b(Costantini et al , 2016aCostantini 2016). On the lower surface of the original PaLASTra model an abrupt contour change was imposed at x∕c = 80% ( Fig.…”
Section: The Two-dimensional Wind Tunnel Model Palastramentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies by Constantini et al [29,30] have shown that care must be taken when interpreting transition results obtained using TSP and applying a temperature step. Their work has shown that when the surface temperature (T w ) is greater than the adiabatic–wall temperature (T aw ), then the transition location can vary depending on the T w /T aw ratio.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with zero pressure gradient, favorable pressure gradient (hereafter referred to as FPG) significantly stabilizes the boundary layer in both incompressible and compressible flows (the first mode as well as Mack's second mode). This is supported by a number of studies, e.g., with direct numerical simulation [5,10,18], linear stability theory [4,6,7] and very recent experiments [23,25]. Hence, in the review by Reed et al [9], the instability of boundary layer with FPG is described as "very weak, if it exists at all".…”
mentioning
confidence: 89%